2019
DOI: 10.1590/0103-8478cr20180930
|View full text |Cite
|
Sign up to set email alerts
|

Optimal size of experimental plots of papaya trees using a modified maximum curvature method

Abstract: This study aimed to evaluate the optimum plot size for the papaya crop by using the modified maximum curvature method under soil and climatic conditions of the Recôncavo Baiano. The experiment comprised a uniformity test using the CNPMF-L78 strain developed by Embrapa Mandioca and Fruticultura, planted at a spacing of 3 m x 2 m, with 16 central rows and 22 plants per row, totaling 352 plants and an area of 2,112 m2. The following parameters were evaluated: plant height and diameter; height of insertion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Size and shape of experimental plots have been discussed by several papers. Sousa et al (2016, Guimarães et al (2019a, 2019b and Silva et al (2019) reported a reduction in CV with increasing plot size. However, after determining the optimum plot size, no significant increase in precision has been reported with increasing plot size (CARGNELLUTI FILHO et al, 2018).…”
Section: Relation Between Relative Information and Coefficient Of Variationmentioning
confidence: 96%
“…Size and shape of experimental plots have been discussed by several papers. Sousa et al (2016, Guimarães et al (2019a, 2019b and Silva et al (2019) reported a reduction in CV with increasing plot size. However, after determining the optimum plot size, no significant increase in precision has been reported with increasing plot size (CARGNELLUTI FILHO et al, 2018).…”
Section: Relation Between Relative Information and Coefficient Of Variationmentioning
confidence: 96%
“…Therefore, to ensure sampling representativeness to evaluate experiments is necessary to consider the arrangement and the plant species within a silvopastoral system (Albrecht and Kandji, 2003;Nair et al, 2009;Oliveira et al, 2016a). Different models have already used heterogeneity in the soil (Lorentz et al, 2010;Li, 2019;Pereira et al, 2017;Saste and Sananse, 2015;Silva et al, 2019). While the modified maximum curvature (MMC) method correlates the ideal number of samples with the coefficient of variation (Facco et al, 2018;Pereira et al, 2017;Silva et al, 2019), the Hatheway method estimates the minimum difference between the treatments determining the optimal number of repetitions per plot (Donato et al, 2018;Mello et al, 2004).…”
Section: Introductionmentioning
confidence: 99%